Abstracts 2018
DOI: 10.1136/bmjopen-2018-ems.22
|View full text |Cite
|
Sign up to set email alerts
|

22 Presence of family in resuscitation in prehospital: the physicians’ and nurses’ opinion

Abstract: hospital causes. Overall 8 cases out of 29 (27.6%) scored between 2.4 and 2.8 (1=Definitely avoidable, 2=Strong evidence of avoidability), 8 cases (27.6%) scored between 3.0 and 4.6 (3=Probably avoidable, 4=Possibly avoidable), and the remaining 13 cases (44.8%) between 4.0 and 5.8 (5=Slightly avoidable or 6=Definitely not avoidable). Variation between raters was satisfactory with ICC 0.84 (95% CI: 0.73 to 0.92). Common themes among cases with strong evidence of avoidability were symptoms or physical findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
4
1
0
Order By: Relevance
“…The results showed that the score of the personnel members' attitudes towards FPDR was lower than the mean value. These results are in line with the results of the studies which were conducted in Turkey [11] and Portugal [33] which they reported that the majority of prehospital emergency personnel members disagreed with the family presence during resuscitation. Furthermore, the results of other studies have indicated that most of the EMS team members do not prefer to provide resuscitation in the presence of the patents' family members and a large number of them feel uncomfortable about resuscitating the patients in the presence of their family members [9,10].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results showed that the score of the personnel members' attitudes towards FPDR was lower than the mean value. These results are in line with the results of the studies which were conducted in Turkey [11] and Portugal [33] which they reported that the majority of prehospital emergency personnel members disagreed with the family presence during resuscitation. Furthermore, the results of other studies have indicated that most of the EMS team members do not prefer to provide resuscitation in the presence of the patents' family members and a large number of them feel uncomfortable about resuscitating the patients in the presence of their family members [9,10].…”
Section: Discussionsupporting
confidence: 89%
“…The other relevant factors included the family members' interference in the process of resuscitation, the prolongation of the resuscitation process, the di culty in making decisions to terminate the resuscitation process, and the increase in the personnel members' emotional stress. These results support the results of the studies conducted by Amaral et al [33] and Belpomme et al [9]. Likewise, some other studies have reported that the personnel' feeling of being under surveillance [11,34], the family members' interference in the personnel members' operation [10,33] and the family members' stress [33] constitute the factors which prompt the personnel to adopt negative attitudes towards FPDR.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations